2020
DOI: 10.1007/s11581-020-03688-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural, impedance and electrochemical double-layer capacitor characteristics of improved number density of charge carrier electrolytes employing potato starch blend polymers

Abstract: Potato starch (PS)/graphene oxide (GO) blend-based solid polymer electrolyte has been doped with lithium trifluoromethanesulfonate (LiCF 3 SO 3 ) via casting method. Lithium-based system is further infused with ionic liquid, 1-butyl-3-methylimidazolium chloride ([Bmim][Cl]) as a plasticizer to form a PS/GO/LiCF 3 SO 3 /[Bmim][Cl] electrolyte with improved conductivity characteristic. The ionic liquid-based polymer electrolyte PS/GO/LiCF 3 SO 3 /[Bmim][Cl] exhibits better physical properties based on structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 125 publications
(155 reference statements)
0
11
0
Order By: Relevance
“…It was proven that ion pairs could block the ion transportation through the polymer electrolyte, therefore impacting the degree at which ions are adsorbed at the carbon pores. Accordingly, this drops the growth of ion adsorption at the electrodes-electrolyte boundaries and thus reduces the C spe value [ 1 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was proven that ion pairs could block the ion transportation through the polymer electrolyte, therefore impacting the degree at which ions are adsorbed at the carbon pores. Accordingly, this drops the growth of ion adsorption at the electrodes-electrolyte boundaries and thus reduces the C spe value [ 1 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are many earlier studies reported for ionic and electronic transference number measurements. 39 46…”
Section: Resultsmentioning
confidence: 99%
“…The ESW of the electrolyte is composed of the working voltage limits in which the electrolyte can work safely without decomposing in a device. As shown in Figure 9, the ESW for the SPE film was 1.99 V, which is adequate for the application of the SPE in electrochemical energy storage devices [74][75][76], for example, in a supercapacitor. Hamsan et al [29] found the ESW of 1.88 V for the system of potato starch/methyl cellulose/NH 4 NO 3 /glycerol and used the electrolyte for an EDLC application.…”
Section: Electrochemical Stability Studymentioning
confidence: 93%